CUSTOMER MOTIVATIONS FOR THE USE - APPAYA, KAVIRAJ (My University, 2011)
The purpose of this research was to identify the motivators of multiple banking for the retail banking sector in Mauritius. The research included both qualitative and quantitative studies. The main finding of the research was the identification of nine motivational factors of multiple banking in the retail banking sector in Mauritius. These motivational factors are: 1. ‘Corporate image’; 2. ‘Prestige and personal’; 3. ‘Lack of trust’; 4. ‘Absence of relationships’; 5. ‘Diversification’; 6. ‘Convenience’; 7. ‘Service quality’; 8. ‘Network building’; and 9. ‘Fees’. The research did not identify distinct groups of multiple bankers but found that the population of multiple bankers is homogeneous. However significant differences were found in the way different demographic groups are motivated. Age, sex, income level and job position were found to play a part in motivating customers to use multiple banking
MBA - WBS
Keywords: Banks and banking, Mauritius